Fast Fashion Assessment Tool: A Case Study of a Moroccan Apparel Supply Chain - Abdelmounaim AGGOUR; Abderrahmane Moussaid; Ahmed Abou El Hassan (International Journal of Supply Chain Management, 2018)
In order to increase their profit margins and international expansion, many international fashion brands implemented a new supply chain strategy named fast fashion. It is a strategy that aims to rapidly get the trendiest fashion clothes in the stores. Several Moroccan fashion retailers tried to copy the fast fashion business model in order to get a responsive supply chain and a high profit margin. Thus, they need a practical tool to ensure that the fast fashion elements are properly implemented. This paper develops an assessment tool using a maturity evaluation model. This maturity assessment tool has been tested at a Moroccan fast fashion retailer. This pilot test adopted a qualitative research methodology with data collected using semi-structured interviews from a single retailer case operating in Moroccan apparel industry. The fast fashion assessment tool enables fashion retailers managers to have a view of the implementation progression and to eventually locate problems and mobilise other tools and mechanisms to explore them.